1996
DOI: 10.1095/biolreprod55.5.1179
|View full text |Cite
|
Sign up to set email alerts
|

β-Mercaptoethanol Enhances Blastocyst Formation Rate of Bovine in Vitro-Matured/in Vitro-Fertilized Embryos1

Abstract: The objectives of this research were to determine the effects of beta-mercaptoethanol (beta-ME) and fetal bovine serum (FBS) on in vitro development of bovine embryos derived from oocytes matured and fertilized in vitro and to examine the mechanism through which beta-ME may influence embryo development. A 2 x 2 factorial treatment arrangement was used to evaluate the effect of 0 or 100 microM beta-ME and 0% or 10% FBS on embryos cultured in Medium 199 (M199) in the absence of somatic cells. Embryos were random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
1
4

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 29 publications
0
34
1
4
Order By: Relevance
“…Species variations and the nutritional requirements of different embryos may have led to the observed differences. The effect of β-ME on living cells is associated with the biosynthesis of intracellular glutathione (GSH), which protects cells against deleterious effects that are followed by oxidative injuries [15]. The simultaneous use of these two antioxidants in our experiments resulted in a higher number of blastomeres in treated embryos compared to the control (E-ctr group).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Species variations and the nutritional requirements of different embryos may have led to the observed differences. The effect of β-ME on living cells is associated with the biosynthesis of intracellular glutathione (GSH), which protects cells against deleterious effects that are followed by oxidative injuries [15]. The simultaneous use of these two antioxidants in our experiments resulted in a higher number of blastomeres in treated embryos compared to the control (E-ctr group).…”
Section: Discussionmentioning
confidence: 73%
“…Supplementation of bovine culture medium with vitamin C improved the porcine denuded oocyte maturation and blastocyst rate after parthenogenetic activation [13]. β-mercaptoethanol (β-ME) is also known as a low molecular weight antioxidant that is usually used in culture media, especially embryonic stem cell culture media [14,15]. In an effort to refine culture media for vitrifiedwarmed embryos, supplementation of culture media with β-ME resulted in lower DNA fragmentation in vitrifiedwarmed bovine blastocysts [16].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Geshi et al [16] showed that 10 µM βME in a co-culture system improves embryo development and Cammano et al [15] did not observed any difference between a low (10 µM) or high (100 µM) concentration of βME in development of resulting embryos. In addition, Geshi et al [16], Caamano et al [14] and Feuagang et al [23] reported better promoting effect of βME when added at 4-8 cell, 8-16 cell and beyond the morula stages, respectively. Therefore, it seems that the apparent differences among studies could be attributed to the culture conditions or developmental stage in which βME has been added.…”
Section: Discussionmentioning
confidence: 97%
“…Following cryopreservation, oocytes and embryos become especially more sensitive to the oxidative stress, resulting in lipid peroxidation, membrane injury and structural destruction [3,23,24]. Low molecular-weight thiol compounds, such as βME, maintain the redox state of cells and protect them against the harmful effects of oxidative injuries and a number of studies have indicated the promoting effects of βME during in vitro embryo production [14][15][16][17][18]. However, data on the effect of βME are conflicting or inconsistent regarding favorable concentration of βME used in culture medium, and regarding the stage of IVP in which βME supplementation better supports embryo development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation